Using Software Applications To Enhance E-Government Service Delivery In Botswana - Bukohwo Michael Esiefarienrhe; Malebogo Mokeresete (Journal of Information System and Informatics, 2022)
Scholars, the ICT community, and policy experts argue that ICT benefits have not been harnessed by most citizens in developing countries, particularly Botswana, due to lack of indigenous software applications for e-commerce, health, customer services, and mismanagement of the ICT infrastructures. Considering the huge investment of public funds on broadband fibre hub, acquization of ICT infrastructures, various committees and sub-committees setup for the management of these infrastructures, it should be expected the the country is well equipped to become the centre for ICT hub in Africa, which unfortunately is not so. Thus, researchers and the media have decried the lack of ICT infrastructure utilization and lack of software applications to utilize the vast infrastructures. To ascertain these reports and better understand the situation, there is a need to holistically research into the ICT project's activities. The mixed research methodology was used in this research which comprised qualitative and quantitative methods for data collection and analysis to gain an in-depth understanding of the broadband development services and users' experiences in Botswana. Also used is the Object-Oriented Analysis and Design (OOAD) methodology with a specific method known as Rapid Application Development (RAD), which enables the researchers to develop software prototypes for Children quickly -Parents Immunisation Alert, License Examination Booking System, and End-user query register as a consequent of the survey conducted that identified these applications as urgently needed to turn around the service delivery and improve on ICT access across the country. The local software developed in this research is expected to boost economic activities and provides a platform for users to adequately utilize the facilities and thus turn the ICT project of Botswana into the type that benefits its populace and creates employment for its youth.